2017
DOI: 10.4103/ijmr.ijmr_1356_15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical & immunological characteristics in systemic lupus erythematosus patients

Abstract: Background & objectives:Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which affects females more than males. Gender affects the manifestations of SLE and men with lupus show more severe symptoms and worse prognosis. This study was aimed to compare clinical and immunological features in female and male lupus patients in Iran.Methods:Demographic, clinical and laboratory data from 78 women and 20 men with lupus were collected. Autoantibodies (against nRNP, Sm, SSA, SSB, Ro-52, CENP, Jo-1, Scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
4
22
0
1
Order By: Relevance
“…Nawata et al and Wang et al reported that high titer of anti-dsDNA is associated with hematuria, proteinuria, elevated serum creatinine, nephrotic syndrome, and hypertension [42,43]. Rasten et al reported that anti-dsDNA significantly increased in male patients with lupus nephritis [44]. Despite several previous studies pointed to the importance of anti-dsDNA in SLE, little data showed the combined effect of anti-dsDNA, antinucleosome, and anti-histone antibodies on kidney affection.…”
Section: Discussionmentioning
confidence: 99%
“…Nawata et al and Wang et al reported that high titer of anti-dsDNA is associated with hematuria, proteinuria, elevated serum creatinine, nephrotic syndrome, and hypertension [42,43]. Rasten et al reported that anti-dsDNA significantly increased in male patients with lupus nephritis [44]. Despite several previous studies pointed to the importance of anti-dsDNA in SLE, little data showed the combined effect of anti-dsDNA, antinucleosome, and anti-histone antibodies on kidney affection.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of NPSLE is reported in many epidemiological studies and has suggested differences in both NPSLE and SLE, based on age, sex, and ethnicity. There is a greater incidence of neurological manifestations in females, and seizure risk is reported higher in males than females [ 9 ]. NPSLE is more frequently reported in African descendants and Asians as compared to white individuals; however, the severity of NPSLE is reported more in White patients [ 10 , 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, studies conducted from different nations have shown that male SLE patients had more severe disease patterns and worse prognoses compared with females. For instance, renal involvement, especially type IV LN with nephrotic syndrome, was more frequent in males [239][240][241][242][243][244][245][246][247].…”
Section: Lupus Nephritis (Ln)mentioning
confidence: 99%